The Use of Educational Media Snakes and Ladders Dental Health in Improving Dental and Oral Health Knowledge of Students of Class 3 Madrasah Ibtidaiyah II City of Palembang - Masayu Nurhayati; Listrianah; Yufen Widodo (PT FORMOSA CENDEKIA GLOBAL, 2022)
Dental and oral health problems are experienced by many school-age children. The cause is less parental knowledge. The purpose of this study was to increase children's knowledge of maintaining oral and dental hygiene. this method uses pretest-posttest. The target is 30 Madrasah students. The results showed that the use of snakes and ladders educational media about dental and oral hygiene increased knowledge and changed attitudes before playing snakes and ladders media. From the snake and ladder game, it is proven that it can increase the knowledge of 3rd grade Madrasah students in maintaining oral and dental hygiene. This can be seen from the results of the pretest-posttest and evaluations that have been carried out.